Branding Produk Melalui Kemasan Kreatif : Pendampingan UMKM Virgin Coconut Oil (VCO Bu Kun) dalam Menarik Konsumen melalui Desain Kemasan yang Eye-Catching - Iswati Iswati; Bayu Ardiwansyah; Heri Cahyono; Kuliyatun Kuliyatun; Cahaya Khaeroni; Prabowo Adi W; Tazakia A. Salma; Naina K. Nufus; Afan A. Kusuma (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
This community service program aimed to enhance the competitiveness of the Virgin Coconut Oil (VCO) product owned by the "Bu Kun" MSME located in RT 11, Yosodadi Sub-district, through a branding strategy based on creative and attractive packaging design. The main problem faced by the MSME was the simple packaging, which failed to reflect the product’s quality and benefits. The program was implemented in several stages, including initial observation, discussion with the MSME, packaging design planning, and implementation of new bottle and label packaging with eye-catching visuals and natural colors. The assistance also included branding education to strengthen product identity and increase consumer loyalty. The results showed increased professionalism among the MSME actors and positive consumer responses, evidenced by rising sales through social media and local marketplaces. This program is expected to serve as a model for empowering other MSMEs in optimizing local product potential through design and targeted branding approaches.